SPATIOTEMPORAL CHARACTERISTICS AND TRENDS OF HEAT EXTREMES IN LAO CAI PROVINCE, VIETNAM - Ngoc Hung, Dao; Bich Diep, Tran; Thuy Nga, Ly; Thi Hong Tuyet, Bui; Thi Phuong, Cu (HNUE Journal of Science: Journal of Natural Sciences, 2026)
Heat extremes are among the most significant manifestations of climate change, posing increasing risks to human health, agriculture, and socio-economic activities. This study analyzes the characteristics and long-term trends of heat extremes in the Lao Cai region, northern Vietnam, over the period 1975 - 2024 using daily maximum temperature data from meteorological observation stations. The occurrences of hot days and heat waves were identified based on threshold-based indices and consecutive-day criteria. The results reveal a clear intensification of heat extremes, with significant increases in the frequency, intensity, and duration of hot days and heat waves, particularly in low-elevation areas. In contrast, stations located at elevations above 900 m experience minimum hot days, indicating a strong influence of topography on the spatial distribution of thermal extremes. Heat extremes exhibit strong seasonality, occurring mainly during the warm season from May to September. These findings demonstrate that mountainous regions such as Lao Cai are increasingly affected by extreme heat and provide a crucial scientific basis for heat risk assessment and climate adaptation planning.